Accuracy of a Rapid Multiplex Polymerase Chain Reaction Plus a Chromogenic Phenotypic Test Algorithm for Detection of Extended-Spectrum β-Lactamase and Carbapenemase-Producing Gram-Negative Bacilli in Positive Blood Culture Bottles. (23rd September 2021) - Ong, Sean Wei Xiang; Hon, Pei Yun; Wee, Sharon Syn Hui; Chia, Jonathan Wei Zhong; Mendis, Shehara; Izharuddin, Ezlyn; Lin, Ray Junhao; Chia, Po Ying; Sim, Rees Chin Swee; Chen, Mark I-Cheng; Chow, Angela; Yoong, Joanne; et al.
Abstract: We studied the performance of an algorithm combining multiplex polymerase chain reaction with phenotypic detection of extended-spectrum β-lactamases and carbapenemases directly from positive blood culture bottles in patients with gram-negative bacteremia and found good concordance with routine cultures. Such an algorithm may be a tool to improve time to optimal therapy in patients with gram-negative bacteremia.